The progress and prospect of sentinel lymph node mapping in endometrial carcinoma - Shi, Jiayan; Shi, ZhiXian; Chen, Qianrun; Bian, Ce (Frontiers in Medicine, 2023)
Sentinel lymph node (SLN) refers to the initial site of the lymphatic drainage from a primary tumor area. Identifying the SLN and analyzing tumor involvement can predict the status of the remaining lymph nodes. Accordingly, sentinel lymph node mapping (SLN mapping) has been brought up and widely applied to cancer therapy for its illuminating role in clinical lymph node resection. Sufficient information to guide surgical pathological staging and adjuvant treatment in endometrial cancer can be rendered by SLN mapping, hence minimizing surgery injury and reducing the incidence of complications. Evidence suggests that using SLN mapping does not affect progression-free survival (PFS) and overall survival (OS) of endometrial cancer patients. Furthermore, there is increasing evidence that using SLN mapping has a high detection rate (DR), sensitivity, and negative predictive value (NPV) for patients with early-stage lower-risk endometrial cancer. This review aims to systematically summarize the advances and application prospects of SLN mapping in endometrial cancer, with an expectation of furnishing reference for the clinical application.